Sand behavior characterization for various grain size distributions - Abd. Rahman, Siti Khalijah (2010)
The enormous amount of work done so far do not much elaborate the relationships both density and fabric to grain size distribution. The main objective of this study is to investigate sand behavior characterization for various grain size distributions. Grain size distribution curves are develop from the sieve analysis. A series of laboratory test has been carried out shows that grain size distributions make an effect on sand behavior characterization. 2 sample of well graded and 1 sample of uniform sample have been tested under wide range of laboratory conditions. Consolidated undrained triaxial test on granular soils have been systematically carried out. The various of stress-strain relationship has been develop during this study. Results of the test clearly indicate that, well graded soil sample have higher strength value than the uniform soil sample. Liquefaction strength of coarse grains may be roughly evaluated by the index of relative density (Dr). despite large different in particle gradations. One of most important mechanisms in the deformation of coarse grains is the relative sliding between particles.